Mathematical modeling of modified atmosphere package/LDPE film combination and its application to design breathing cylinders for extending the shelf life of green asparagus - Wen-Chien Lu; Yu-Tsung Cheng; Chien-Jung Lai; Been-Huang Chiang; Ping-Hsiu Huang; Po-Hsien Li (Chemical and Biological Technologies in Agriculture, 2023)
Abstract Background The O2 levels in food packaging systems play an essential role in the deterioration of food quality and shelf life. Modified atmosphere packaging (MAP) supports the storage of fresh and processed foods by inhibiting chemical and physical changes while reducing the deterioration caused by microorganisms. Materials and methods This study established and validated the equations for the relationship between MAP formulation reagents, asparagus respiration, permeability of packaging film, and rates of O2 and CO2 mass transfer in which different interactions occur and affect each other. Results The resulting atmosphere of packaging was determined to be the key to achieving the MAP benefits. The active MAP formulations developed in this study were combined with very-low-density polyethylene films to store green asparagus spears. During storage, the combined films effectively maintained the firmness of green asparagus spears, fiber, and vitamin C content, and outperformed the passive MAP and control groups. The above results confirm all the equations in the passive and active MAP systems established in this study. Conclusions Hence, maintaining the asparagus quality with an active MAP treatment will reduce economic loss and possibly provide new insights into applying active MAP retail packages to preserve fruits and vegetables in post-harvest shelf life. Graphical Abstract